Penerapan Strategis PLTS Skala Industri dalam Pembangunan Energi Bersih dan Ekonomi Hijau di Kawasan Tropis - Paris Manarira Sitanggang; Choislee Purba; Kristian Sihombing; Riean Wijaya; Brimen Mikhael Manurung (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Tropical regions offer significant opportunities in the development of renewable energy, particularly through industrial-scale Solar Power Plants (PLTS). This study aims to analyze PLTS implementation strategies in tropical areas as a means to support clean energy and green economic development. A literature study with a qualitative-descriptive approach was employed. The results show that industrial-scale PLTS implementation is highly promising due to stable and high solar radiation throughout the year. However, challenges persist such as limited infrastructure, high initial capital, and inconsistent regulatory frameworks. Thus, collaboration among stakeholders is essential to establish a sustainable energy ecosystem.